Integration and Summation Together !

Calculus Level 5

Let I n = cos ( n x ) ( 1 + x 2 ) 2 d x \displaystyle I_{n} = \int_{-\infty}^{\infty}\frac{\cos(nx)}{(1+x^{2})^{2}}dx . If n = 0 I n = A \displaystyle \sum_{n=0}^{\infty} I_{n} = A , find 100 A \lfloor 100A \rfloor .

Notation : \lfloor \cdot \rfloor denotes the floor function .


The answer is 393.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let I ( a , b ) = 0 sin ( a x ) x ( x 2 + b ) d x \displaystyle I(a,b)=\int_{0}^{\infty}\frac{\sin(ax)}{x(x^{2}+b)}dx

So we have :-

I a = 0 cos ( a x ) x 2 + b d x \displaystyle \frac{\partial I}{\partial a} = \int_{0}^{\infty}\frac{\cos(ax)}{x^{2}+b} dx

2 I a 2 = 0 x sin ( a x ) x 2 + b d x = 0 sin ( a x ) x d x + b 0 sin ( a x ) x ( x 2 + b ) d x = π 2 + b I ( a , b ) \displaystyle \frac{\partial^{2}I}{\partial a^{2}} = -\int_{0}^{\infty}\frac{x\sin(ax)}{x^{2}+b}dx= -\int_{0}^{\infty} \frac{\sin(ax)}{x}dx + b\int_{0}^{\infty}\frac{\sin(ax)}{x(x^{2}+b)} dx = -\frac{\pi}{2} + bI(a,b)

Here I used the fact that 0 sin ( a x ) x = π 2 \displaystyle \int_{0}^{\infty}\frac{\sin(ax)}{x} = \frac{\pi}{2}

So we have ( D 2 b ) I = π 2 \displaystyle (D^{2}-b)I = \frac{-\pi}{2} Here D a \displaystyle D\equiv \frac{\partial}{\partial a} and D 2 2 a 2 \displaystyle D^{2}\equiv \frac{\partial^{2}}{\partial a^{2}}

Solving this ODE in a we get

I ( a , b ) = C 1 e a b + C 2 e a b + π 2 b \displaystyle I(a,b) =C_{1}e^{a\sqrt{b}} + C_{2}e^{-a\sqrt{b}} +\frac{\pi}{2b} We have I ( 0 , b ) = 0 I(0,b) = 0

So C 1 + C 2 + π 2 b = 0 \displaystyle C_{1}+C_{2} + \frac{\pi}{2b} = 0

Also I a = b ( C 1 e a b C 2 e a b ) \displaystyle \frac{\partial I}{\partial a} = \sqrt{b}(C_{1}e^{a\sqrt{b}} -C_{2}e^{-a\sqrt{b}})

Also I a \displaystyle \frac{\partial I}{\partial a} at ( 0 , b ) = (0,b)= 0 d x x 2 + b = π 2 b \displaystyle \int_{0}^{\infty}\frac{dx}{x^{2}+b} = \frac{\pi}{2\sqrt{b}} .

So we get C 1 = 0 \displaystyle C_{1}=0 and C 2 = π 2 b \displaystyle C_{2} = \frac{-\pi}{2b}

So I ( a , b ) = π 2 b e a b + π 2 b \displaystyle I(a,b) = \frac{-\pi}{2b}e^{-a\sqrt{b}} + \frac{\pi}{2b}

I a = π 2 b e a b \displaystyle \frac{\partial I}{\partial a } = \frac{\pi}{2\sqrt{b}}e^{-a\sqrt{b}}

2 I b a = π 4 ( a e a b b + e a b b b ) \displaystyle \frac{\partial^{2} I}{\partial b \partial a} = \frac{-\pi}{4}\left(\frac{ae^{-a\sqrt{b}}}{b} +\frac{e^{-a\sqrt{b}}}{b\sqrt{b}}\right)

From the Definition of I ( a , b ) I(a,b) we have

2 I b a = 0 cos ( a x ) ( x 2 + b ) 2 d x \displaystyle \frac{\partial^{2} I}{\partial b \partial a} = \int_{0}^{\infty} \frac{-\cos(ax)}{(x^{2}+b)^{2}}dx

We know cos ( n x ) ( x 2 + 1 ) 2 d x = 2 0 cos ( n x ) ( x 2 + 1 ) 2 d x \displaystyle \int_{-\infty}^{\infty} \frac{\cos(nx)}{(x^{2}+1)^{2}} dx = 2\int_{0}^{\infty}\frac{\cos(nx)}{(x^{2}+1)^{2}}dx

So what we need is 2 2 I b a \displaystyle -2\frac{\partial^{2} I}{\partial b \partial a} at the point ( n , 1 ) (n,1) .

So Using the expression above we have I n = π 2 ( n + 1 ) e n \displaystyle I_{n} = \frac{\pi}{2}(n+1)e^{-n} .

We know 1 1 x = n = 0 x n \displaystyle \frac{1}{1-x} = \sum_{n=0}^{\infty}x^{n} for 1 < x < 1 -1<x<1

Hence x 1 x = n = 0 x n + 1 \displaystyle \frac{x}{1-x} = \sum_{n=0}^{\infty}x^{n+1}

Differentiating term by term once on both sides (possible due to uniform convergence)

We have 1 ( 1 x ) 2 = n = 0 ( n + 1 ) x n \displaystyle \frac{1}{(1-x)^{2}} = \sum_{n=0}^{\infty}(n+1)x^{n}

Using the above we have n = 0 I n = A = π 2 e 2 ( e 1 ) 2 = 3.931159 \displaystyle \sum_{n=0}^{\infty}I_{n} =A= \frac{\pi}{2}\cdot \frac{e^{2}}{(e-1)^{2}} = 3.931159

Hence 100 A = 391 \displaystyle \lfloor 100A \rfloor =391

Note 1:- The function s i n ( a x ) x ( x 2 + b ) \frac{sin(ax)}{x(x^{2}+b)} is continuous for all x and all a and b>0. The partial derivative to it is continuous for all x and a and b>0. The improper integral of the function is uniformly convergent for all a by M-test .The improper integral of the partial derivative of the function is uniformly convergent for all positive a a .Hence justification of interchange of derivative and integral sign is valid as these form a sufficient set of conditions for us to do so.

Note 2:- I have used the operator method for finding the solution to the ordinary differential equation in terms of a a using auxiliary equations,complimentary functions and particular integrals. These are pretty standard things and can be found in any elementary level differential equations book.

Usually People Use Residue Theorem to solve this kind of problem but I did it using Feynmann Technique and found it very interesting as it leads to many generalizations. Please upvote if you liked the problem and the solution !.

How did you write 0 x sin ( a x ) x 2 + b d x = 0 sin ( a x ) x d x + b 0 sin ( a x ) x 2 + b d x \displaystyle -\int_{0}^{\infty}\frac{x\sin\left(ax\right)}{x^{2}+b}~dx=-\int_{0}^{\infty}\frac{\sin\left(ax\right)}{x}~dx+b\int_{0}^{\infty}\frac{\sin\left(ax\right)}{x^{2}+b} ~dx ?

Vilakshan Gupta - 11 months, 2 weeks ago

Log in to reply

Multiply above and below by x and then add and substract b. 0 x sin ( a x ) ( x 2 + b ) d x = 0 x 2 sin ( a x ) x ( x 2 + b ) d x = 0 ( x 2 + b b ) sin ( a x ) x ( x 2 + b ) d x = 0 ( sin ( a x ) x b sin ( a x ) x 2 + b ) d x \displaystyle \int_{0}^{\infty}\frac{x\sin(ax)}{(x^{2}+b)}dx =\int_{0}^{\infty} \frac{x^{2}\sin(ax)}{x(x^{2}+b)}dx = \int_{0}^{\infty} \frac{(x^{2}+b-b)\sin(ax)}{x(x^{2}+b)}dx =\int_{0}^{\infty} \left(\frac{\sin(ax)}{x} -\frac{b\sin(ax)}{x^{2}+b}\right)dx

Arghyadeep Chatterjee - 11 months, 2 weeks ago

Log in to reply

But you can't split improper integrals like that!

Vilakshan Gupta - 11 months, 2 weeks ago

Log in to reply

@Vilakshan Gupta I have already given the explanation in the note as they are uniformly convergent. You can prove it using M-Test. A convergent integral can be split into two integrals provided both of them converge separately.Since the improper integral of both sin(ax)/x and sin ( a x ) x 2 + b \frac{\sin(ax)}{x^{2}+b} is convergent so we can split it into two parts. In general any limit of (f(x)+g(x)) can be written as limit of f(x) + limit of g(x) provided both f(x) and g(x) converge separately. watch this :-https://www.youtube.com/watch?v=WP8JMVGuOD8

Arghyadeep Chatterjee - 11 months, 2 weeks ago
Chew-Seong Cheong
Jun 27, 2020

We can solve I n = e i n x ( 1 + x 2 ) 2 d x = ( cos ( n x ) ( 1 + x 2 ) 2 d x ) \displaystyle I_n = \int_{-\infty}^\infty \frac {e^{inx}}{(1+x^2)^2} dx = \Re \left(\int_{-\infty}^\infty \frac {\cos (nx)}{(1+x^2)^2} dx \right) using contour integration with a semicircle of radius R R \to \infty in the upper complex plain.

e i n z ( 1 + z 2 ) 2 d z = e i n x ( 1 + x 2 ) 2 d x + arc e i n z ( 1 + z 2 ) 2 d z \oint \frac {e^{inz}}{(1+z^2)^2} dz = \int_{-\infty}^\infty \frac {e^{inx}}{(1+x^2)^2} dx + \int_{\text{arc}} \frac {e^{inz}}{(1+z^2)^2} dz

By Jordan's lemma, the last integral in the RHS above approaches 0 0 as R R \to \infty . Then

e i n x ( 1 + x 2 ) 2 d x = e i n z ( 1 + z 2 ) 2 d z = e i n z ( ( z i ) ( z + i ) ) 2 d z Only 1 pole z = i is within the contour. = 2 π i d d z [ e i n z ( z + i ) 2 ] z = i By Cauchy integral formula = 2 π i [ e i z ( i n z n 2 ) ( z + i ) 3 ] z = i = π e n ( n + 1 ) 2 \begin{aligned} \int_{-\infty}^\infty \frac {e^{inx}}{(1+x^2)^2} dx & = \oint \frac {e^{inz}}{(1+z^2)^2} dz \\ & = \oint \frac {e^{inz}}{((z-i)(z+i))^2} dz & \small \blue{\text{Only 1 pole }z=i \text{ is within the contour.}} \\ & = 2\pi i\cdot \frac d{dz} \left[\frac {e^{inz}}{(z+i)^2} \right]_{z=i} & \small \blue{\text{By Cauchy integral formula}} \\ & = 2\pi i \left[\frac {e^{iz}(inz-n-2)}{(z+i)^3} \right]_{z=i} \\ & = \frac {\pi e^{-n}(n+1)}2 \end{aligned}

I n = ( e i n x ( 1 + x 2 ) 2 d x ) = π e n ( n + 1 ) 2 \displaystyle I_n = \Re \left( \int_{-\infty}^\infty \frac {e^{inx}}{(1+x^2)^2} dx \right) = \frac {\pi e^{-n}(n+1)}2 .

Then

A = n = 0 π e n ( n + 1 ) 2 = π 2 n = 1 d x n d x x = e 1 = π 2 d d x n = 1 x n x = e 1 = π 2 d d x [ x 1 x ] x = e 1 = π e 2 2 ( e 1 ) 2 3.931 \begin{aligned} A & = \sum_{n=0}^\infty \frac {\pi e^{-n}(n+1)}2 = \frac \pi 2 \sum_{n=1}^\infty \frac {d x^n}{dx} \bigg|_{x = e^{-1}} = \frac \pi 2 \cdot \frac d{dx} \sum_{n=1}^\infty x^n \bigg|_{x = e^{-1}} = \frac \pi 2 \cdot \frac d{dx} \left[\frac x{1-x} \right]_{x = e^{-1}} = \frac {\pi e^2}{2(e-1)^2} \approx 3.931 \end{aligned}

Therefore 100 A = 393 \lfloor 100A\rfloor = \boxed{393} .


Reference: Cauchy integral formula

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...